2019
DOI: 10.1017/s0021932019000312
|View full text |Cite
|
Sign up to set email alerts
|

‘This sickness is not hospital sickness’: a qualitative study of the evil eye as a source of neonatal illness in Ghana

Abstract: Previous research has described the evil eye as a source of illness for pregnant women and their newborns. This study sought to explore the perceptions of the evil eye among mothers whose newborns had experienced a life-threatening complication across three regions of Ghana. As part of a larger, quantitative study, trained research assistants identified pregnant and newly delivered women (and their newborns) who had survived a life-threatening complication at three tertiary care hospitals in southern Ghana to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Erroneous beliefs about causes of illnesses in SYIs such as linking illnesses to a child's given name were also common. Our findings are similar to studies conducted elsewhere in low-and middle-income countries where illnesses or death to children have been attributed to PLOS ONE the 'evil eye' or malevolent spirits [7,10,[29][30][31]. A study in the Ashanti Region of Ghana revealed how caregivers attributed pregnancy loss and newborn mortality to a local illness called asram-believed to be caused by evil spirits [11].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Erroneous beliefs about causes of illnesses in SYIs such as linking illnesses to a child's given name were also common. Our findings are similar to studies conducted elsewhere in low-and middle-income countries where illnesses or death to children have been attributed to PLOS ONE the 'evil eye' or malevolent spirits [7,10,[29][30][31]. A study in the Ashanti Region of Ghana revealed how caregivers attributed pregnancy loss and newborn mortality to a local illness called asram-believed to be caused by evil spirits [11].…”
Section: Discussionsupporting
confidence: 88%
“…Studies on this subject have noted that perceptions of causes of illnesses in SYIs may vary across socio-cultural and economic contexts [6][7][8]. In some communities, newborn and young infant illnesses and deaths are attributed to supernatural forces such as evil spirits or punishment from God [7,[9][10][11]. Individuals, families, and communities may also attribute illnesses to natural or biomedical causes such as poor environmental and sanitation conditions, personal hygiene, and biological factors [12] as well as social-related reasons such as violation of taboos [13].…”
Section: Introductionmentioning
confidence: 99%
“…While several studies have identified concerns about evil spirits as a driver for women to conceal pregnancies in Gambia and elsewhere across SSA [ 27 ], the context of evil spirits have been under-explored in in-depth qualitative terms as they relate specifically to ANC access. Better understanding of how such spirits are held to operate, drawn from anthropological literature and ethnographic studies, may help healthcare practitioners identify the women most likely to fear such situations and who accordingly choose to conceal their pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Duly handicapped by the blinders that envy places on them, enviers are therefore unable to see that “escape” is possible, and that those who succeeded in “escaping” did so without pulling others down. The unfortunate consequence of these “pulling down” behaviors on a society's development is to foreclose the exchange of knowledge, creativity, and economic resources at both the individual and systemic levels since individuals, organizations, and identity groups operate from a fear of falling victim to the evil eye or witchcraft (Apostolides & Dreyer, 2008; Bell et al., 2020; Schoeck, 1966; H. F. Stein, 1974) should the knowledge of their possession of an ability and/or accomplishment of envy become public.…”
Section: The Anatomy Of the Phd Syndromementioning
confidence: 99%